Dynamics of Changes in the Representative Structure in the MPR RI Post-Amendment of the 1945 Constitution of the Republic of Indonesia and Its Implications for the Function of the State Representative Institution - Rosando, Rosando; KMS Herman (Jurnal Multidisiplin Indonesia, 2025)
This study examines the dynamics of changes in the representative structure in the People’s Consultative Assembly (MPR) of the Republic of Indonesia after the amendment to the 1945 Constitution of the Republic of Indonesia, especially related to the elimination of the Group Representative element in MPR membership. This change has a significant impact on the existence of the MPR as a state representative institution, both in relation to its role and function in the Indonesian state system. This study aims to analyze the implications of the elimination of the Group Representative on the function of people’s representation, as well as its impact on the legislative process and political decision-making in Indonesia. With a legal analysis approach, this study reveals how these changes reflect the evolution of the representative system in Indonesia and assess whether the MPR can still carry out its functions effectively in the context of post-reform democracy.